Antibacterial Therapy, Utilizing Oil Extracts from Corn Waste - S. Ciobanu (Romanian Society of Oral Rehabilitation, 2010)
The usage of "Izofural" 0.05%, obtained out of waste oil corn, determines the reduction of bacterial plaque, the diminishing or even the disappearance of pain, gingivitis, edema, reduction. In the study there were treated 30 patients, 13 male and 17 female, ages 20 - 55 years, with periodontal disease (gingival of different forms, chronic marginal periodontitis). Izofural exceeds furacilini 2-20 times, to different species of Staphylococcus and Streptococcus. As the result of clinical studies, Izofural 0.05% has proved to be an efficient remedy, with pronounced anti-inflammatory effects. It is easy to use, non-allergic, without negative side effects, cheap and beneficial to dentistry.